Generation of supersonic solitions by earthquake emission in the van Allen rediation belt - Mofiz, U. A.; Battiston,Roberto (BRAC University, 2010)
The parametric coupling between earthquake emitted circularly polarized electromagnetic radiation and ponderomotively driven ion-acoustic perturbations in the Van Allen Radiation Belt is considered. A cubic nonlinear Schrödinger equation for the modulated radiation envelope is derived, and then solved analytically. Supersonic solitons are found to be generated in the Van Allen Belt which can be a tool for the prediction of a massive earthquake to be followed.